Object unified identifier method in logistics resource integration - Huiqi Zhu; Hanping Hou (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: The status which many programs for object identifier are not incompatible with each other has become a bottleneck for integrating logistics resources. Scholars have done some relevant studies in terms of coding and conversion mechanisms, but the problem still has not got a better solution. The purpose of this study is to research how to make the object identifier programs Compatible. Design/methodology/approach: Author proposed object unified identifier (OUID) method based on OID and introduced the standard identification code in it, according to the problems of object identifier in logistics resource integration. And the paper further designed the acquisition process of the resource basic information and location information, and analyzed application environment of object unified identifier based on OID. Findings: OUID made up for the lack of location information in conversion mechanism, and avoided to promote new unified identifier standards at the same time. The supplement of the application environment provided an important support to solve the problems of poor communication caused by non-unified object identifier in the process of logistics resource integration. Originality/value: Using this method, each identification systems not only keep its own territory, but also can compatible with other object identifiers.
Keywords: 650; logistics resource integration; object identifier; object unified identifier